Forensic Pathology Reviews - Tsokos, Michael; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
Over the last decade, the field of forensic science has expanded enormously with the rapid emergence of new autopsy and laboratory techniques, and the identification of many new markers for specific pathological conditions. In Forensic Pathology Reviews, Volume 2, leading national and international forensic pathologists provide cutting-edge accounts of special topics from various fields of forensic pathology and death scene investigation. These critical surveys concentrate on common pathological entities likely to be encountered in daily forensic routine, as well as on specific pathological conditions rarely seen in the autopsy room. Complementing rather than replacing the classic textbooks in forensic pathology, the authors explore new avenues for analyzing the pathology of death from starvation (child neglect), head injuries inflicted by glass bottles, the clinical and pathological features of primary cerebral neoplasms, obesity as it is relevant to the forensic pathologist, and infant and early childhood asphyxial death. Other areas of interest covered include suicide, viral myocarditis in sudden death cases, curious death scene phenomena (hiding, covering, and undressing), forensic entomology, the interpretation of toxicological findings, anabolic-androgenic-steroid abuse, and autopsy findings of subendocardial hemorrhages. A comprehensive review of the international literature that is otherwise difficult to assemble is given for each chapter. Cutting-edge and concise, Forensic Pathology Reviews, Volume 2 offers forensic investigators a rich demonstration of how the latest medical and scientific advances are being applied to solve current problems of high interest to forensic pathologists today.
Death From Environmental Conditions -- Death as a Result of Starvation -- Trauma -- Skull Injuries Caused by Blows With Glass Bottles -- Forensic Neuropathology -- Primary Cerebral Neoplasms as a Cause of Sudden, Unexpected Death -- Death From Natural Causes -- Obesity Epidemic in the United States -- Child Abuse, Neglect, and Infanticide -- Infant and Early Childhood Asphyxial Deaths -- Suicide -- Complex Suicides -- Occupation-Related Suicides -- Infectious Diseases -- Sudden, Unexpected Death Related to Viral Myocarditis -- Death Scene Investigation -- Human Primitive Behavior -- Forensic Entomology -- Arthropods and Corpses -- Toxicology -- Practical Toxicology for the Forensic Pathologist -- Performance-Enhancing Drugs -- Long-Term Effects of Anabolic-Androgenic-Steroid Abuse -- Forensic Differential Diagnosis -- Subendocardial Hemorrhages.
Keywords: Medicine; Forensic medicine; Medicine & Public Health; Forensic Medicine; Electronic books